Governing immigration through crime : a reader - Dowling, Julie A., 1975-; Inda, Jonathan Xavier (Stanford Social Sciences, an imprint of Stanford University Press, 2013)
In the United States, immigration is generally seen as a law and order issue. Amidst increasing anti-immigrant sentiment, unauthorized migrants have been cast as lawbreakers. Governing Immigration Through Crime offers a comprehensive and accessible introduction to the use of crime and punishment to manage undocumented immigrants. Presenting key readings and cutting-edge scholarship, this volume examines a range of contemporary criminalizing practices: restrictive immigration laws, enhanced border policing, workplace audits, detention and deportation, and increased policing of immigration at the state and local level. Of equal importance, the readings highlight how migrants have managed to actively resist these punitive practices. In bringing together critical theorists of immigration to understand how the current political landscape propagates the view of the "illegal alien" as a threat to social order, this text encourages students and general readers alike to think seriously about the place of undocumented immigrants in American society